Journal Quality and Ecosystem initiative helps support UMP 25 Strategic Plan - Shalfarina, Shahriman; Safriza, Baharuddin (2022)
PEKAN, 27 January 2022 - Universiti Malaysia Pahang (UMP) Press, through the UMP Journal Quality and Ecosystem initiative, is taking steps and strategies in supporting the UMP 25 Strategic Plan, which targets a significant increase in UMP-issued journals in the world’s prestigious bibliographic database by 2025.